ASPEK BIOLOGI DAN HABITAT IKAN LURAI (Corica soborna Hamilton, 1822) DARI HILIR SUNGAI MAHAKAM, KALIMANTAN TIMUR [Biological Aspects and Habitat of Lurai Fish (Corica soborna Hamilton, 1822) from the Lower Mahakam River, East Kalimantan] - Jusmaldi, Jusmaldi; Nuramelia, Nadira; Arif, Muhammad Fauzi; Hendra, Medi; Rukmi, Dijan Sunar; Rosadi, Imam (BRIN Publishing (Penerbit BRIN), 2023)
The Lurai fish, scientifically known as Corica soborna Hamilton, 1882, belongs to the small freshwater fish in the Clupeidae family of the Clupeiformes order. Local communities in the lower Mahakam River, East Kalimantan, have long exploited this species for consumption and trade. At the same time, the biological information regarding this fish, which forms the fundamental basis for its conservation, is yet unknown. This study aimed to analyze the biological aspects and habitat of the lurai fish in the lower Mahakam River. A total of 812 fish samples were analyzed using measuring and weighing methods. The results showed that the fish's length ranged from 42.48 to 63.89 mm and their weight from 0.70 to 2.56 g. Mature lurai fish with 52.48-54.47 mm length dominated the highest mode. The regression model of the length-weight relationship was W= 5×10-6L3.18 for the total sample. The growth pattern of the fish was isometric, and the relative condition factor ranged from 0.765 to 1.123. The sex ratio was 1 male : 1.68 females. The highest percentage of gonadally mature fish was found in February. Fish lengths at first gonad maturity ranged from 52.55 to 53.38 mm for males and 59.94 to 61.25 mm for females. The habitat of the lurai fish is at the edge of the river with vegetation, a muddy bottom, a dissolved Oxygen range of 3.70-4.17 mgL-1, a temperature range of 27.50-28.40 °C, a TDS range of 50-80 mgL-1, a clarity range of 19-29 cm, a water depth range of 2.80-3.60 m, and a current velocity range of 0.65-1.07 mst-1.